Bioprocess development for anti-hypertensive drug Ajmalicine production by suspension-cultured cells of Catharanthus roseus in a bioreactor - AJAY G. NAMDEO,; DEVANAND P. FULZELE, (International Journal of Pharma and Bio Sciences, 2018)
The objective of this study was to determine the effect of agitation speed of the helix impeller on growth and alkaloid production in a bioreactor. The agitation rate of the helix impeller on growth and ajmalicine production by Catharanthus roseus suspension cultures in the 7 lit and 50 lit bioreactors was investigated. The suspension cultures cultivated in the bioreactor at different agitation rate in the range of 80 to 180 rpm. The agitation speed at 180 rpm of the impeller found detrimental to growth, while low favored the cell aggregates and sediment at bioreactor bottom. Batch mode operation performed in a 50 lit bioreactor, the impeller swiftness at 140 rpm proven to be better for growth and achieved the highest biomass of 25.18 g/l dry weight which corresponds to 325.75 g/l fresh weight. HPLC analysis revealed that suspension cultures stirred at 140 rpm enhanced ajmalicine production (48.63 mg/l) on day 20. However, trace amount of ajmalicine secretedin the culture medium. The present study demonstratespracticable scale up and ajmalicine production in a bioreactor.